Invasão biológica de Solanum elaeagnifolium Cav. (Solanaceae) na América do Sul frente às mudanças climáticas - Renato Luiz Fernandes (2021)
Biological invasions are among the most important threats to global biodiversity, and tend to increase with global warming. Solanum elaeagnifolium Cav. (Solanaceae) is a shrub with an amphitropical native distribution in the Americas, recognized as an aggressive invasive species in several regions of the planet, causing economic impacts mainly in agriculture. This research outlined an overview of biological invasions and estimate the areas of environmental suitability of S. elaeagnifolium in the present and made predictions of the future distribution of the species in South America, in the context of climate change. For this, we evaluated 2 IPCC scenarios, an optimistic (RCP4.5) and a pessimistic (RCP8.5), for 2 time periods, 2041-2060 and 2061-2080, using ecological niche models. Our results indicated an increase in climatically suitable areas for the establishment of the species in both scenarios, especially in the scenario of higher increase in global temperature, where the species may occupy areas of high ecological relevance for conservation. We also report, for the first time, the occurrence of the species for Brazil, the country that should be the most affected by the expansion of the species on the continent. We emphasize the importance of the work to support actions to monitor and prevent the invasion of the species S. elaeagnifolium in the region, avoiding or reducing its environmental and economic impacts.